Anogenital distance in adult women is a strong marker of endometriosis: results of a prospective study with laparoscopic and histological findings. Issue 3 (6th June 2020) - Crestani, A; Arfi, A; Ploteau, S; Breban, M; Boudy, A-S; Bendifallah, S; Ferrier, C; Darai, E
Abstract: STUDY QUESTION: Could anogenital distance (AGD) be a non-invasive marker of endometriosis and correlated to the American Society for Reproductive Medicine revised score (r-ASRM) and ENZIAN classifications? SUMMARY ANSWER: Surgically and histologically proven endometriosis is associated with a short AGD in women of reproductive age but not correlated either to the severity or to the location of the disease. WHAT IS KNOWN ALREADY: AGD is a marker of intrauterine androgen exposure and exposure to oestrogen-like chemicals such as phthalates. Moreover, exposure to endocrine disruptors, such as organochlorine chemicals, is associated with endometriosis. It has been suggested that a short AGD in women is associated with an increased risk of endometriosis based on clinical and ultrasound exams. STUDY DESIGN, SIZE, DURATION: A prospective cohort study was conducted from January 2018 to June 2019 in a tertiary-care centre including 168 adult women undergoing pelvic surgery. PARTICIPANTS/MATERIALS, SETTING, METHODS: Of the 168 women included, 98 patients had endometriosis (endometriosis group) and 70 did not (non-endometriosis group). An operator (not the surgeon) measured the distance from the clitoral surface to the anus (AGD-AC) and from the posterior fourchette to the anus (AGD-AF) before surgery using a millimetre accuracy ruler. Endometriosis was diagnosed on exploration of the abdominopelvic cavity, and the r-ASRM and ENZIAN scores were calculated. All removed tissues underwent pathological examination. MAIN RESULTS AND THE ROLE OF CHANCE: Mean (±SD) AGD-AF measurements were 21.5 mm (±6.4) and 32.3 mm (±8.1), and average AGD-AC measurements were 100.9 mm (±20.6) and 83.8 mm (±12.9) in the endometriosis and non-endometriosis groups ( P  < 0.001), respectively. Mean AGD-AF and AGD-AC measurements were not related to r-ASRM stage ( P  = 0.73 and 0.80, respectively) or ENZIAN score ( P  = 0.62 and 0.21, respectively). AGD-AF had a better predictive value than AGD-AC for discriminating the presence of endometriosis (AUC = 0.840 (95% CI 0.782–0.898) and 0.756 (95% CI 0.684–0.828)), respectively. For AGD-AF, an optimal cut-off of 20 mm had a specificity of 0.986 (95% CI 0.923–0.999), sensitivity of 0.306 (95% CI 26.1–31.6) and positive predictive value of 0.969 (95% CI 0.826–0.998). In multivariable analysis, the diagnosis of endometriosis was the only variable independently associated with the AGD-AF ( β  = −9.66 mm 95% CI −12.20–−7.12), P  < 0.001). LIMITATIONS, REASONS FOR CAUTION: The sample size was relatively small with a high proportion of patients with colorectal endometriosis reflecting the activity of an expert centre. Furthermore, we did not include adolescents and the AGD-AF measurement could be particularly relevant in this population. WIDER IMPLICATIONS OF THE FINDINGS: The measurement of AGD could be a useful non-invasive tool to predict endometriosis. This could be especially relevant for adolescents and virgin women to avoid diagnostic laparoscopy and empiric treatment. STUDY FUNDING/COMPETING INTEREST(S): None.